A Data-Driven Training Kit to Enhance the Note Recording Skills of Music Learners - Chantanasut, Thaworada (Bright Publisher, 2025)
Music note recording is a fundamental skill in music education, yet many undergraduate learners struggle due to the lack of structured, self-guided practice resources. This study aimed to develop and evaluate a data-driven training kit designed to Enhance the Note Recording Skills of Music Learners. A total of 20 first-year students from a Bachelor of Education program in Western Music and Vocal Education were selected through purposive sampling. Research instruments included the training kit, expert evaluation forms, pre- and post-tests, student satisfaction surveys, and behavior observation checklists. Quantitative data were analyzed using mean, standard deviation, and paired sample t-tests. Results showed a statistically significant improvement in students' performance after the intervention (t = 18.789, p .001), with a large effect size (Cohen’s d = 2.53). Experts rated the kit highly (M = 4.86, SD = 0.29), and students reported very high satisfaction (M = 4.94, SD = 0.14). These findings support the kit’s effectiveness as an engaging and pedagogically sound tool for developing music note recording skills in higher education settings.